Short Gamma-Ray Bursts as Manifestation of Collisions of Primordial Black Holes with Stars - Zhilyaev, B.E. (Известия Крымской астрофизической обсерватории, 2007)
Short Gamma-Ray Bursts as Manifestation of Collisions of Primordial Black Holes with Stars